Sosialisasi Media Pembelajaran Anak Tunanetra Reading Interaction Console With Kinetic Intelligence Braille Versi Prototipe: Pengembangan Media Pembelajaran Anak Inklusif - Ricki Ananda; Muhammad Amin; Muhammad Iqbal Haitame Tambunan; Saifuddin Muhammad Jalil (STMIK Royal, 2026)
Abstract: The Reading And Interaction Console With Kinetic Intelligence – Braille prototype aims to introduce an innovative educational technology for blind students at SLB Negeri Kota Tanjungbalai. The school, under the authority of the Province of North Sumatra, has 111 students across elementary, junior high, and senior high school levels. SLBN Tanjungbalai is led by Mrs. Resti, S.Pd., supported by 13 teachers and 1 administrative staff member. This media integrates an interactive kinesthetic system, binary Braille sensors, and artificial intelligence (AI) capable of recognizing Braille letter patterns based on tactile input and providing real-time voice feedback. Braille letters are converted into six-dot binary codes (Braille-cell), such as A (100000), B (110000), C (100100), D (100110), up to Z (101011). These binary combinations are detected by tactile sensors or push buttons, then processed by an ESP32S connected to a 2004 LCD with I2C, a DFPlayer Mini, and a speaker to produce the corresponding letter sounds. The socialization activity was conducted at SDLB Negeri Kota Tanjungbalai, involving companion teachers and eight blind students. The activities included device demonstration, usage training, and interactive trials. The results show positive responses from both teachers and students, as the media enhances motivation, accuracy, and speed in learning Braille letters. RICKI-Braille proved to be more interactive and adaptive compared to conventional Braille learning media. Keywords: Braille; visually impaired; inclusive learning media; assistive technology inclusive education; Abstrak: Media Reading And Interaction Console With Kinetic Intelligence – Braille versi prototipe bertujuan memperkenalkan inovasi teknologi pendidikan bagi peserta didik tunanetra di SLB Negeri Kota Tanjungbalai. Sekolah yang berada di bawah naungan Provinsi Sumatera Utara ini memiliki 111 siswa dari jenjang SD, SMP, hingga SMA. SLBN Tanjungbalai dipimpin oleh Ibu Resti, S.Pd., dengan dukungan 13 guru dan 1 tenaga tata usaha. Media ini memadukan sistem kinestetik interaktif, sensor Braille biner, dan kecerdasan buatan (AI) yang mampu mengenali pola huruf Braille berdasarkan input titik-titik taktil, kemudian memberikan umpan balik suara secara real-time. Huruf Braille dikonversi menjadi kode biner enam titik (Braille-cell), misalnya A (100000), B (110000), C (100100), D (100110), dan seterusnya hingga Z (101011). Sensor taktil atau push button membaca kombinasi biner tersebut, lalu memprosesnya melalui ESP32S yang terhubung dengan LCD 2004 + I2C, DFPlayer Mini, dan speaker untuk menghasilkan suara huruf yang sesuai. Sosialisasi dilakukan di SDLB Negeri Kota Tanjungbalai dengan melibatkan guru pendamping dan delapan siswa tunanetra. Kegiatan mencakup demonstrasi alat, pelatihan penggunaan, serta uji coba interaktif. Hasilnya, guru dan siswa memberikan respons positif karena media ini meningkatkan motivasi, ketepatan, dan kecepatan belajar huruf Braille. RICKI-Braille terbukti lebih interaktif dan adaptif dibanding media Braille konvensional. Kata kunci: Braille; tunanetra; media pembelajaran inklusif; teknologi asistif; pembelajaran inklusif